English-medium instruction in Tunisia: Perspectives of students - Abdeljaoued, Marii (Frontiers in Psychology, 2023)
Within the globalization and the internationalization of education practices and universities and given the global status of English in the world, English as a medium of instruction (EMI) is a needed asset. This necessitates joining the wagon of using English for instruction. Hence, the rapid proliferation of EMI in universities across the globe. Only recently have EMI programs started in leaps and bounds in Tunisia. This is perhaps due to the resistance of academia and the lack of traditions to use EMI. Given the recent adoption of EMI in some Tunisian higher education institutes, the research area is unchartered. In this vein, this timely study hopes to find out how students perceive using English as a medium of instruction. It will also delve into the challenges they encounter and the strategies to circumvent such obstacles. The case study involved data collection via a survey and classroom observation. It was found that students have a positive attitude towards and an awareness of its importance. It was found that students adopt translanguaging strategies to ensure effective interaction with content teachers and better assimilation of academic content.